Implementasi Learning Organization Pada Sekolah Menengah Pertama Negeri - Oktavianda, Baharya Gama Ramadhito; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Learning Organization is one of the strategies for developing and enhancing the quality of human resources within an organization. This research aims to understand the implementation of the Learning Organization at SMPN 1 Mantup using Senge's theory, which focuses on five components or sub-foci of the Learning Organization: (1) Personal Mastery, (2) System Thinking, (3) Mental Models, (4) Shared Vision, and (5) Team Learning. This qualitative research employs a descriptive approach with data collection methods including interviews, observations, and document studies. Interviews were conducted with the school principal, teachers, and administrative staff at SMPN 1 Mantup. The results of this research indicate that SMPN 1 Mantup has implemented the Learning Organization strategy quite effectively. This is evident from the successful implementation of all five components or sub-foci of the Learning Organization, marked by the fulfillment of all indicators within these components through programs, activities, and individual initiatives. However, there are areas for improvement in the implementation of the Learning Organization at SMPN 1 Mantup, such as enhancing existing Learning Organization programs and creating and implementing key performance indicators for each program and activity. Abstrak Learning organization adalah salah satu strategi dalam mengembangkan dan meningkatkan kualitas sumber daya manusia yang ada pada sebuah organisasi. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi learning organization yang dilaksanakan pada SMPN 1 Mantup dengan menggunakan teori learning organization yang dikemukakan oleh Senge yang berfokus pada 5 komponen atau subfokus learning organization yaitu: (1) Personal mastery, (2) system thinking, (3) mental models, (4) shared vision, (5) team learning. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif dengan metode pengumpulan data melalui wawancara, observasi, dan studi dokmentasi. Wawancara dilakukan kepada kepala sekolah, guru, serta anggota tata usaha yang ada pada SMPN 1 Mantup. Hasil dari penelitian ini menunjukkan SMPN 1 Mantup telah melaksankan strategi learning organization dengan cukup baik hal ini terlihat dari terlaksananya dengan baik kelima komponen atau sub-fokus dari learning organization yang ditandai dengan terpenuhinya seluruh indikator yang ada pada kelima komponen tersebut melalui program, kegiatan, serta aktivitas individu yang ada didalamnya.